2012
DOI: 10.5455/jice.20120315032524
|View full text |Cite
|
Sign up to set email alerts
|

Incidental radiological finding of charm needles in the hip region: a potential surgical precaution

Abstract: We report an unusual incidental radiographic finding of this 71 year old Malay lady who suffered a closed neck of femur fracture due a fall at home which had undergone total hip replacement at our establishment .This is one of the only papers showing incidental occurrence of susuk or charm needles in hip region in orthopaedic field. [J Intercult Ethnopharmacol 2012; 1(1.000): 66-67

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The threat of foreign bodies in modern day surgical practice is evident. Migration of these substances causing vascular and nerve injuries in the extremities have been reported [7,11]. These foreign bodies also cause increase risk of infection whether immediately upon insertion or at a later date, which requires their surgical removal.…”
Section: Discussionmentioning
confidence: 99%
“…The threat of foreign bodies in modern day surgical practice is evident. Migration of these substances causing vascular and nerve injuries in the extremities have been reported [7,11]. These foreign bodies also cause increase risk of infection whether immediately upon insertion or at a later date, which requires their surgical removal.…”
Section: Discussionmentioning
confidence: 99%
“…2 Apart from the maxillo-facial complex, they are often reported in the thorax, chest, abdomen, breasts, spine, mons pubis and limbs. 2,8 Susuks are generally pin-or needle-shaped, measuring around 0.5 mm in diameter and between 0.5 and 1.0 cm in length. 3 Balasundaram et al conducted chemical analysis that revealed the components of susuks as containing <90% gold and other metals such as aluminium, iron, copper and silicon.…”
Section: Discussionmentioning
confidence: 99%
“…5 The number of needles inserted may vary, as it is considered that more needles increases the magical potency. 8 Nambiar et al conducted a study in which 1-39 needles were reported in the craniofacial region. Prior to this, Oon discovered 1-47 needles per patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jarum karisma atau dalam bahasa seharihari disebut dengan "susuk" adalah suatu struktur mirip jarum logam yang terbuat dari emas atau logam mulia lain, disematkan pada jaringan lunak tubuh, yang berfungsi sebagai jimat. 1,2 Fenomena pemasangan susuk banyak ditemukan pada masyarakat Asia Tenggara, diantaranya Malaysia, Brunei, Singapura, Thailand, dan Indonesia. 2,3 Jimat berbentuk jarum tersebut dipasang dengan berbagai tujuan seperti: kesuksesan, kekayaan, awet muda, kecantikan, kharisma, kewibawaan, dan sebagai perlindungan dari penyakit atau bahaya.…”
Section: Pendahuluanunclassified